FENOMENA ALAS KAKI DALAM KARYA SENI GRAFIS DENGAN TEKNIK SERIGRAPHY - ADE RUSDI, Dr.Budiwirman, M.Pd Drs. Irwan, M.Sn (Serupa The Journal of Art Education, 2014)
Phenomena are things that can be seen with the sense of sight as happens in footwear , footwear phenomenon in human life that goes on in daily life, like a phenomenon ofbarefoot in the house, stealing footwear, footwear pitching , and are associated with aberrant human behavior.This work was produced after passing through various processes and inspired many of the things that often authors see everyday that sometimes the writer 's own experience . The desire of the authors is that the work can be understood byeveryone.Then the production of a work which is entitled " Footwear Phenomenon In Graphic Art Work With serigraphy technique " the author will present the forms , concepts , revealed ways , and the media with a greater emphasis on the use of serigraphy techniques which printing process is done by using a silk or nylon cloth called monyl . Pores left open so that the ink can pass and the pores are not used covered with gelanthine / ulano / bremol that for sweeping inks or paints used rubber blade or squeegee . Keyword :Phenomena, Footwear, Graphic Art Work.